The actuality of qualitative research and its challenges at Al-Quds University, as perceived by a representative sample of university professors and student researchers - Shuibat, Mohammad Awad; Abu Ziyad, Natasha Omar; Alkhateeb, Nayef AbdAlraouf (Journal of Educational and Psychological Sciences, 2023)
This study aimed to reveal the reality of qualitative research and its challenges at Al-Quds University from the point of view of a sample of professors and research students at the university. (14) Participants from faculty members and doctoral students at the university.The results concluded that the reality of qualitative research at Al-Quds University from the point of view of a sample of professors and students’ researchers at the university is represented in four basic topics, which were named (scarcity, dissatisfaction, desire, need). The data analysis reached the challenges of qualitative research at Al-Quds University from the point of A sample of professors and students researchers at the university looked at three topics, which were named (a cultural challenge, an academic challenge, and a challenge of qualitative research characteristics). In view of the research results, a number of recommendations were made, most notably the need to support qualitative research production by the Deanship of Scientific Research financially and morally, due to the cost, effort and skills it needs.
Keywords: Al-Quds University; The Reality of Qualitative Research; Case Study; Challenges of Qualitative Research